THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE INDUSTRIAL SECTOR AND ITS INFLUENCE ON HUMAN RESOURCES IN INDUSTRIAL MANAGEMENT - Rismaja Putra (CV. Radja Publika, 2025)
Artificial Intelligence (AI) has become a key element in industrial transformation, bringing significant changes in operational processes, management, and innovation. This study aims to explore the role of AI in various industrial sectors, including automation, data analysis, logistics management, and product development. This study uses a descriptive qualitative research method by collecting research data through observation, interviews and literature studies. The results of the study show that the application of AI can increase efficiency, productivity, and the quality of industrial output as a whole. However, on the other hand, the adoption of this technology also has a major impact on human resources (HR). This study found that AI shifts the need for labor from manual skills to technology-based skills, creating the need for reskilling and upskilling. In addition, this shift presents social challenges, such as the potential for structural unemployment due to the reduction of routine job roles. However, AI also opens up new opportunities, such as jobs in data analysis and AI-based system management. This study concludes that the role of AI in industry must be balanced with strategic policies that support HR development, to ensure that this transformation has a positive impact on sustainability. This includes training programs, increasing access to technology, and adapting to changes in the work ecosystem in the digital era.